Reproductive characteristics of adolescents from Mirim de Marília Legion – São Paulo, Brazil, 2005 - Rojas, Sílvia Helena CC; Crestani, Karin D; Batista, Gabriela V; Melo, Ana Paula A (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: the knowledge of the personal, socioeconomic and reproductive characteristics of the adolescents from Legião Mirim in Marília - SP, offeredus subsidies for the planning of actions in reproductive health addressed to this institution. Objective: To describe the personal, socioeconomic and reproductivecharacteristics emphasizing the use of contraceptive methods and the prevention of sexually transmitted diseases. Methods: this study belongs to the field ofthe epidemiology, applied to the diagnosis of the adolescents’ health from 16 to 18 years old. The data were obtained through a structured questionnaire. Theanalysis was accomplished through the software Epi Info version 3.3.2. Results: 47,1% of the 136 adolescents interviewea, referred to present beginning ofsexual activity with an average of 15,5 years old. The majority declared to be brownish and Catholic. None was married or in stable union, although, 45,3%declared having sexual relationships in a regularly way. There was an increase of 18,1% when we compared the current use of the oral contraceptive with itsuse in the first sexual relationship. The use of the masculine condom presented a decrease of 50,4%, there was an increase of 32,3% in the association of both.When STDs are concerned, 100% of the adolescents interviewed declared knowing them. Aids was the most mentioned (89,0%). To prevent STDs theydeclared to make use of masculine condoms and having a fixed partner. The prevention of these identified the importance of the use of the masculine condomand of having fixed partner. Conclusion: this study highlights that a significant percentage of adolescents assume risk behavior by having sexual relationshipswithout protection, increasing the woman’s vulnerability to precocious pregnancy and STD.